Prevalence, Awareness and Associated Risk Factors of Diabetes among Adults in Xi’an, China - Hu, Meiqin (Sci Rep, 2017)
The study aimed to investigate the prevalence, awareness, treatment and glycaemic control of diabetes and its associated risk factors among adults in Xi’an, China. We collected data among participants aged 18 years or older through a self-developed questionnaire and an additional health examination. A total of 8150 participants were included, with an overall prevalence of diabetes of 8.0%. Among 655 participants with diabetes, 52.5% were aware they had diabetes, 48.1% took antidiabetic treatment, and 19.1% had their fasting blood glucose level at less than 7.0 mmol/l. Older age, lower educational level, higher body mass index, larger waist circumference, having an unhealthy diet and having more comorbidities were positively associated with the risk of diabetes. Participants who were older, who had higher education and who had more comorbidities were more aware that they had diabetes. Being older age, having higher education and having more comorbidities were also factors for better treatment. Participants who were older were more likely to have their glucose level controlled. The prevalence of diabetes among adults in Xi’an is high, with suboptimal awareness, treatment, and glycaemic control rates. Comprehensive integrated strategies based on risk factors should be implemented to improve the prevention and glycaemic control of diabetes.